IgE-mediated soy protein sensitization in children with cow’s milk allergy - Agustina Santi; Mohammad Juffrie; Sumadiono Sumadiono (Indonesian Pediatric Society, 2012)
Background Soy-based formula as an alternative to cow's milkformula is preferable to extensively hydrolyzed protein formulabecause of the lower cost and more acceptable taste. However,cow's milk allergy patients can subsequently develop a sensitivityto soy protein.Objective To compare soy protein sensitization in children withand without an allergy to cow's milk.Methods This study was conducted in Yogyakarta from September2007 until March 2008. Subjects were children aged below 4years with an atopic history. Subjects were divided into 2 groups:those with a positive skin prick test to cow's milk and thosewith a negative skin prick test to cow's milk (control group).Both groups were given soy formula and tested at 6 weeks forsensitization to soy.Results There were 45 children in each group. Age, sex, andatopic history were similar in both groups. We found no soyprotein sensitization (negative skin prick results) in all subjectsfrom both groups.Conclusion Risk of immunoglobulin E-mediated sensitizationto soy protein was not proven in children with cow's milk allergy.[Paediatr lndones. 2012;52:67-71).